2002
DOI: 10.1038/ni777
|View full text |Cite
|
Sign up to set email alerts
|

Human Toll-like receptor 4 recognizes host-specific LPS modifications

Abstract: Lipopolysaccharide (LPS) is the principal proinflammatory component of the Gram-negative bacterial envelope and is recognized by the Toll-like receptor 4 (TLR4)-MD-2 receptor complex. Bacteria can alter the acylation state of their LPS in response to environmental changes. One opportunistic bacterium, Pseudomonas aeruginosa, synthesizes more highly acylated (hexa-acylated) LPS structures during adaptation to the cystic fibrosis airway. Here we show that human, but not murine, TLR4-MD-2 recognizes this adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
461
3
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 537 publications
(495 citation statements)
references
References 35 publications
27
461
3
4
Order By: Relevance
“…These results are consistent with a previous study showing that TLR5 is essential to the recognition of P. aeruginosa flagellin both in vivo and ex vivo [38]. P. aeruginosa possesses other virulence factors such as LPS, which is recognized either by TLR2 or TLR4 depending on its structure [23,50]. It has been suggested that the most important system involved in the recognition of P. aeruginosa could be TLR and that TLR4 and TLR5 were redundant for the recognition of P. aeruginosa [38].…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with a previous study showing that TLR5 is essential to the recognition of P. aeruginosa flagellin both in vivo and ex vivo [38]. P. aeruginosa possesses other virulence factors such as LPS, which is recognized either by TLR2 or TLR4 depending on its structure [23,50]. It has been suggested that the most important system involved in the recognition of P. aeruginosa could be TLR and that TLR4 and TLR5 were redundant for the recognition of P. aeruginosa [38].…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the lipid A acylation state may influence outer membrane permeability. In addition, changes in lipid A acylation have been shown to affect complement activation and opsonization, as well as TLR-4 recognition in vitro (1,7,13,21). Despite these compelling data, the influence of lipid A acylation on in vivo host-pathogen interactions is not well understood.…”
mentioning
confidence: 99%
“…MD-2 binds LPS with high affinity (17), and it is required for Tlr4 signaling (11). Although normal expression of the Tlr4 and MD-2 are too low for direct measurements of LPS binding to the receptor complex, indirect evidence of ligandreceptor binding has been provided by the ability of structurally different forms of Tlr4 (18,19) or MD-2 (20,21) to discriminate between differences in lipid A structure. Direct evidence of LPS binding to Tlr4/MD-2 was provided by LPS cross-linking experiments in cells that overexpressed these proteins (22).…”
mentioning
confidence: 99%